THE IMPACT OF THE DIGITAL SYSTEM ON THE MANAGEMENT OF EDUCATIONAL INSTITUTIONS-AN APPLIED STUDY ON UNIVERSITIES - Raghdan Adnan Abdulrazzaq; Alassaad Lakhal (Scholars Digest Publishing, 2025)
This study aimed to assess the influence of Digital Transformation on Change Management in Iraqi universities in , province. To achieve this, it pursued several objectives, including examining the state of Digital Transformation's presence in these institutions, evaluating the status of Change Management, and determining the extent of Digital Transformation's impact on Change Management. Employing a descriptive analytical approach, data were collected through a survey administered to employees. The study's results highlight crucial findings. It reveals a significant interest in Change Management within the surveyed universities, with respondents recognizing the importance of this variable. Additionally, the study indicates a strong interest in Digital Transformation among these universities, with dimensions like 'Digital Transformation Strategy (DTS)' and 'Digital Technology (DT)' showing positive results. The research further uncovers a positive correlation between Digital Transformation and Change Management dimensions, suggesting that enhancing Digital Transformation efforts can lead to more effective Change Management. Notably, Digital Transformation was found to explain approximately 12% of the variation in Change Management, with substantial effects on specific dimensions. Based on these findings, the study recommends that Iraqi universities in, focus on enhancing Change Management by ensuring that employees are well-informed about change objectives and actively involved in the change process.
Keywords: Digital system, enterprise management, education sector.